Rapid jail-based implementation of overdose education and naloxone distribution in response to the COVID-19 pandemic - Carrie B. Oser; Margaret McGladrey; Marisa Booty; Hilary Surratt; Hannah K. Knudsen; Patricia R. Freeman; Danelle Stevens-Watkins; Monica F. Roberts; Michele Staton; April Young; Emma Draper; Sharon L. Walsh (BMC, 2024)
Abstract Background People incarcerated in jails are highly impacted by the opioid epidemic, and overdose education and naloxone distribution (OEND) is an effective strategy to reduce opioid overdose deaths. This study examines barriers and facilitators of fast-track OEND implementation within the jails in the Wave 1 Kentucky counties of the HEALing Communities Study during the COVID-19 pandemic. Methods Meeting minutes with jail stakeholders were qualitatively coded using the Practical, Robust Implementation and Sustainability Model (PRISM) as the coding framework. The analysis highlighted the top barriers and facilitators to fast-track OEND implementation within the PRISM framework. Results Space and staffing shortages related to the COVID-19 pandemic, disruptions in interorganizational programming from pandemic-related service suspensions, and a lack of technological solutions (e.g., reliable Internet access) for socially distanced delivery were the top barriers to fast-track OEND implementation. In addition, there were limitations on non-jail staff access to jails during COVID-19. Top facilitators included jail leadership support, the option to prioritize high-risk groups, and the incorporation of OEND processes into existing communications and management software. While the COVID-19 pandemic strained jail infrastructure, jail and partner agency collaboration led to creative implementation strategies for the successful integration of OEND into jail operations. Urban jails were more likely than rural jails to be early adopters of OEND during the public health emergency. Conclusions Understanding the barriers to and facilitators of OEND within jails will improve implementation efforts seeking to curb opioid overdose deaths. Jail leadership support and interorganizational efforts were key facilitators to implementation; therefore, it is recommended to increase buy-in with multiple agencies to promote success. Challenges brought on by COVID-19 have resulted in a need for innovative solutions for implementation. Clinical trial information ClinicalTrials.gov, NCT04111939, Submitted 30 September 2019, https://clinicaltrials.gov/study/NCT04111939?titles=HEALing%20Communities%20Study&rank=1 .